The Impact of Bacillus subtilis PB6 and Chromium Propionate on the Performance, Egg Quality and Nutrient Metabolizability of Layer Breeders - Otoniel Souza (MDPI AG, 2021)
The objective of this study was to evaluate the effects of Bacillus subtillis PB6, chromium propionate or a combination of the two on the performance, egg and eggshell quality, nutrient metabolizability and serum biochemistry of layer breeders. White Plymouth Rock and Red Rhodes Island breeder hens at 55 weeks of age were allocated in individual cages using a completely randomized block design with 16 replicates. Hens were fed control, control + probiotic (500 g/ton of Bacillus subtilis PB6), control + CrProp (50 g/ton of chromium propionate) and control + probiotic + CrProp diets from 55 to 70 weeks of age. Productive parameters and eggshell quality as well as cortisol and blood biochemistry were grouped each 28 d as well as for the overall period. The metabolizability of nutrients and energy was determined at 70 weeks of age. In the overall period, hens fed the control + probiotic or control + probiotic + CrProp diets had significantly higher egg production, egg mass, shell percentage, thickness and shell strength. The metabolizability of dry matter, nitrogen and energy increased in hens that were fed the control + probiotic + CrProp diet. In conclusion, diets supplemented with Bacillus subtillis PB6 and chromium propionate resulted in improved productive performance, eggshell quality and nutrient metabolizability of layer breeders, without modifying serum cortisol, albumin and triglycerides.